Effect of Moxibustion Therapy at SP6 (Sanyinjiao) Acupressure Point on Labor Pain Intensity During First Stage Active Phase - Andita Rania Salsabila; Anik Purwati; Reny Retnaningsih (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
The active phase of the initial stage of labor is characterized by escalating pain intensity due to uterine contractions and cervical dilation. Inadequate pain management can lead to significant discomfort and stress for laboring women. Preliminary observations at independent midwifery practices Yulis Indriana indicated that most mothers experienced moderate to severe pain during this phase. Nonpharmacological interventions, such as moxibustion therapy at the SP6 (sanyinjiao) acupressure point, may reduce pain. This study aimed to analyze differences in labor pain intensity before and after moxibustion therapy during the active phase. A quasi-experimental study with a non-equivalent control group design was conducted, involving 32 respondents selected through accidental sampling, with 16 in the intervention group and 16 in the control group. Pain intensity was measured using the Numeric Rating Scale (0-10). Data were analyzed using univariate and bivariate methods with a significance level of p < 0.05. The intervention group exhibited a significant reduction in pain intensity from 7.88 ± 0.719 to 5.13 ± 0.957 (p < 0.001), whereas the control group showed no significant change, from 7.69 ± 0.873 to 7.75 ± 0.775 (p = 0.317). A significant difference between groups was also identified (p < 0.001). Moxibustion therapy at SP6 may reduce labor pain intensity and can be considered a complementary intervention in midwifery practice.